Exploration of Barriers and Facilitators to Optimal Emergency Department Care of Sickle Cell Disease: Opportunities for Patient–Physician Partnerships to Improve Care. (2nd January 2021) - Liederman, Zachary; Quartey, Naa Kwarley; Ward, Richard; Papadakos, Janet
Abstract: Sickle cell disease patients commonly present to an emergency department (ED) due to acute vaso-occlusive pain episodes (VOEs), also known as vaso-occlusive crises (VOCs). Unsatisfactory patient care leads to preventable morbidity, mortality, and substantial financial costs. This study investigated the current use of sickle cell disease patient-directed physician education (PDPE) in the clinical setting and also explored opportunities for improvement. A qualitative phenomenologic design was used with semi-structured in-depth interviews. Open-ended questions were used to probe participant's experiences with EDs, the feasibility of a PDPE program as well as barriers and facilitators to PDPE. A total of nine patients and eight physicians participated in the study. Three major themes were identified: divergent challenges to patient recommendations, new targets for sickle cell disease education and triage process: not heard and not seen. Numerous challenges exist to the implementation and optimization of PDPE with sickle cell disease triage processes and nursing support identified as influential factors. Paramount to the process of improving PDPE is physicians perceiving patients as credible sources of information, especially as it relates to generalized concerns of opioid dosing. A patient provided written or digital education tool can be considered to facilitate PDPE to ease communication strain on patients while increasing communication efficiency.